ISOLATION AND IDENTIFICATION OF MAIN AND SIDE PRODUCTS FROM ADDITION REACTION OF CARYOPHYLLENE OXIDE BY FORMIC ACID - M Muchalal; Trisulistyaningsih Rahayu (Indonesian Journal of Chemistry, 2002)
Main and side products from reaction of caryophyllene oxide and formic acid have been isolated using column chromatography with silica gel 60 G as stationary phase and n-hexane : ethyl acetat (9:1, v/v) as mobile phase. The first and second fraction were analyzed using infrared spectrophotometer, gas chromatography, and gas chromatography-mass spectrometer. Caryophyllene formiate as a main product was found in the first fraction. The side product that had been identified were 4,10,10-trimethyl-7-methylenebicyclo[6,2,0]decane-4-carbaldehyde, 2-(9-hydroxy-4,4,8 trimethyltricyclo[6,3,1,01,5]dodecyl)metanoate, clovanediol,4,11,11-trimethyl-8 methylene-3-bicyclo-[7,2,0]-undecen-5-ol,2,5-(6,10,10 imethyltricyclo[7,2,1,01,9]dodecyl)metanedioat, and derivative of caryophylleneformiate.